Factors associated with the progression of mesangial lesions in IgA nephropathy: A comparative analysis of renal re-biopsies - Li, Yetong; Jiang, Shimin; Gao, Hongmei; Yang, Yue; Liu, Xiaorong; Li, Wenge (Frontiers in Endocrinology, 2022)
Objectives: IgA nephropathy (IgAN) is the most common primary glomerular disease, and is the leading cause of chronic renal failure. Because mesangial lesions are the main pathological changes seen in IgAN, we investigated factors associated with the progression of mesangial lesions in IgAN. Methods: We enrolled participants with IgAN who underwent repeat renal biopsies. Based on the progression of mesangial proliferative lesions, the participants were divided into progressive and stable groups. The progression group included participants with a ratio of mesangial cell proliferation score ≥ 1.1 (i.e., proliferation of > 10%) in the second biopsy specimen compared to the first biopsy specimen. The stable group included participants who did not fulfill the aforementioned criteria. We recorded the laboratory parameters, expression of renin-angiotensin system (RAS) receptors (angiotensin II type 1 receptor [AT1R], angiotensin II type 2 receptor [AT2R], Mas receptor [MasR], and the Mas-related G protein-coupled receptor, member D [MrgD]) and mesangial matrix proteins (collagen [Col] IV, fibronectin [FN] and laminin) at the first and second renal biopsies, and the use of immunosuppressive therapy and/or RAS blockers after the first biopsy. Results: We enrolled 24 patients with IgAN who underwent repeat renal biopsies. Half of patients showed progression of mesangial lesions on repeat renal biopsy after a median of 4.3 (1–6) years. The progression group had significantly higher expression levels of AT1R and mesangial matrix proteins (Col IV and FN), and significantly lower expression of AT2R and MasR, compared to the stable group. Multivariate analysis showed that the use of RAS blockers (hazard ratio [HR], 0.27; 95% CI, 0.08–0.97; p < 0.05) and the level of proteinuria (HR, 1.8; 95% CI, 1.04–3.12; p < 0.05) were associated with progression of mesangial lesions. Additionally, the progression group exhibited a more rapid decline of renal function compared to the stable group (0.38 and 0.012 ml/min/1.73 m2/month, respectively; p = 0.004). Conclusions: Continuous activation of the intrarenal RAS and massive proteinuria correlate with histological progression of mesangial lesions in IgAN patients, which may further accelerate the deterioration of renal function.